2009
DOI: 10.1080/10601320902719370
|View full text |Cite
|
Sign up to set email alerts
|

Poly(vinyl alcohol)-based Amphiphilic Copolymer Aggregates as Drug Carrying Nanoparticles

Abstract: A series of amphiphilic polyisobutylene-block-poly(vinyl alcohol) (PIB-b-PVA) copolymers of constant PIB and varying PVA block length was synthesized by living carbocationic polymerization and their solution behavior was studied. The synthesis involved the preparation of polyisobutylene-b-poly(tert.-butyl vinyl ether) followed by hydrolysis with hydrogen bromide. The copolymers were characterized by gel permeation chromatography, 1 H-NMR, and MALDI-TOF MS methods. The micellization behavior of the copolymers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…The obtained spectrum for PVA–PANI is shown in Figure 1 where at δ = 7.3 ppm and δ = 7.5 ppm there is evidence of a doublet of doublets (d, J = 6.5 Hz, C 6 H 4 ) corresponding to the benzenoid and quinoid sections of PANI in emeraldine phase, then δ = 4.7 ppm (s, D 2 O). The doublet located at δ = 3.9 ppm (d, J = 28.5 Hz) corresponds to the characteristic signal of α proton of oxygen binding PVA–PANI, while the multiplet located at δ = 1.5 ppm (m, J = 18.7 Hz) suggests the integration of methylene protons from the PVA backbone [19,20].…”
Section: Resultsmentioning
confidence: 99%
“…The obtained spectrum for PVA–PANI is shown in Figure 1 where at δ = 7.3 ppm and δ = 7.5 ppm there is evidence of a doublet of doublets (d, J = 6.5 Hz, C 6 H 4 ) corresponding to the benzenoid and quinoid sections of PANI in emeraldine phase, then δ = 4.7 ppm (s, D 2 O). The doublet located at δ = 3.9 ppm (d, J = 28.5 Hz) corresponds to the characteristic signal of α proton of oxygen binding PVA–PANI, while the multiplet located at δ = 1.5 ppm (m, J = 18.7 Hz) suggests the integration of methylene protons from the PVA backbone [19,20].…”
Section: Resultsmentioning
confidence: 99%
“…As stated above, this block copolymer was not able to form stable solutions with encapsulated iron oxide NPs alone. Probably, the polar groups contained in the hydrophobic IND molecule make it act as a low molecular surfactant, affecting the structural characteristics and colloidal stability of the mixed self-assembled nanostructures formed [ 23 , 25 , 26 , 27 ]. Regarding the rest of the mixed systems, PLMA 22 - b -POEGMA 32 /NPs/IND was stable for 72 h and PLMA 22 - b -POEGMA 13 /NPs/IND precipitated almost immediately after mixing the initial solutions.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 1(d) the product contains two amide bands (at 1640 and 1700 cm −1 ), amide bands (at 1540 cm −1 ) and -NH-(at 3340 cm −1 ). As shown in Figure 2(d), a new peak at 7.35 ppm was observed, compared with the 1 H-NMR of PLA-NH 2 , which was attributed to the benzene ring of the protective group of (Z)-lysine and the peaks at 5.02 (i, -CH 2 -), 4.20 (f, -CH-), 2.95 (h, -CH 2 -) and 1.35 (g, -CH 2 -) ppm were assigned to protons of the lysine segment. Therefore, both IR and 1 H-NMR spectra showed that the copolymerization had been successfully completed.…”
Section: Copolymerization and Characterization Of Amino-tailed Pla Anmentioning
confidence: 87%
“…Amphiphilic copolymers are well known for their excellent blood compatibility (1)(2)(3)(4), and receive more and more attention for their potential application in tissue engineering and drug delivery (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%